Spectrophotometric Determination of Co(II) in Vitamin B12 Using 2-(biphenyl-4-yl)-3-((2-(2,4-dinitrophenyl) hydrazono)methyl) imidazo [1,2-a]pyridine as Ligand by Flow Injection–Merging Zone Analysis - Mohammed Yaseen, Suhair; Basheer Qassim, Bushra; Owayed Al-Lami, Naeemah (Al-Nahrain Journal of Science, 2020)
Nitro Schiff base ligand of 2-(biphenyl-4-yl)-3-((2-(2,4-dinitrophenyl) hydrazono) methyl) imidazo [1,2-a] pyridine (BDNHMIP) was synthesized, identified and used in spectrophotometric determination of Co(II) at 530nm. The suggested method of Co(II) determination was performed at optimum analytical parameters of 3.2 ml/min flow rate, 137.4L ligand volume, 98.1L Co(II) volume, 1minutes residence time in reaction coil, and as a result 48 sample/hour of method throughput was accomplished. The proposed method performed linearity of 25-400 ppm, molar absorptivity coefficient of 121.5704´103 L.mol.-1cm-1, and L.O.D of 2.28ppm. The suggested method was successful applied for determination of Co(II) content of vitamin B12 injection samples with high recovery of 99.5-100.3% and minimum relative error percent of -0.3 - 0.5%.